Effects of a temperature rise on melatonin and thyroid hormones during smoltification of Atlantic salmon, Salmo salar - Nisembaum, Laura Gabriela; Martin, Patrick; Fuentes, Michael; Besseau, Laurence; Magnanou, Elodie; Mccormick, Stephen; Falcón, Jack (Journal of Comparative Physiology B, 2020)
International audience Smoltification prepares juvenile Atlantic salmon (Salmo salar) for downstream migration. Dramatic changes characterize this crucial event in the salmon’s life cycle, including increased gill Na+/K+-ATPase activity (NKA) and plasma hormone levels. The triggering of smoltification relies on photoperiod and is modulated by temperature. Both provide reliable information, to which fish have adapted for thousands of years, that allows deciphering daily and calendar time. Here we studied the impact of different photoperiod (natural, sustained winter solstice) and temperature (natural, ~ + 4° C) combinations, on gill NKA, plasma free triiodothyronine (T3) and thyroxine (T4), and melatonin (MEL; the time-keeping hormone), throughout smoltification. We also studied the impact of temperature history on pineal gland MEL production in vitro. The spring increase in gill NKA was less pronounced in smolts kept under sustained winter photoperiod and/or elevated temperature. Plasma thyroid hormone levels displayed day–night variations, which were affected by elevated temperature, either independently from photoperiod (decrease in T3 levels) or under natural photoperiod exclusively (increase in T4 nocturnal levels). Nocturnal MEL secretion was potentiated by the elevated temperature, which also altered the MEL profile under sustained winter photoperiod. Temperature also affected pineal MEL production in vitro, a response that depended on previous environmental acclimation of the organ. The results support the view that the salmon pineal is a photoperiod and temperature sensor, highlight the complexity of the interaction of these environmental factors on the endocrine system of S. salar, and indicate that climate change might compromise salmon’s time “deciphering” during smoltification, downstream migration and seawater residence.